DIPG-56. Development and application of a novel antibody against CD99 as a therapeutic strategy in Diffuse Midline Glioma. (3rd June 2022) - Venkataraman, Sujatha; Balakrishnan, Ilango; Madhavan, krishna; Chetty, Senthilnath Lakshmana; Pierce, Angela; Fosmire, Susan; Nuss, Zachary; Coleman, Philip; Green, Adam; Vibhakar, Rajeev
Abstract: BACKGROUND: There is an unmet need to identify novel targeted therapies for Diffuse Midline glioma (DMG) which is currently a refractory disease. Recently, we identified high expression of a cell surface antigen, CD99 in H3K27M-mutant expressing DMGs compared to other normal brain counterparts. We developed a novel chimeric CD99 antibody and tested the anti-tumor efficacy of this antibody in vitro and in vivo. METHOD: Bio-legend cell-surface screening was performed in H3K27M-mutant and WT DMG cells. Functional role of CD99 was studied using CD99 proficient and depleted tumors. Designed and synthesized CD99 antibody with a new binding sequence on a human IgG scaffold and performed cell toxicity and growth-inhibitory studies using DMG tumor and normal cells. We also performed these studies in combination with radiation. Multiple patient-derived orthotopic DMG xenograft models was used to test the antibody efficacy. Different antibody delivery routes, that are clinically relevant were investigated. RESULTS: CD99 expression is transcriptionally regulated by H3K27M and is enriched on the cell surface of K27M tumors compared to WT DMG tumors. Our new CD99 antibody (10D1 clone) significantly reduced DIPG tumor cell proliferation in vitro. Intravenous infusion of this antibody in DIPG tumor bearing mice showed complete clearance of tumor that prolonged animal survival suggesting the enhanced anti-tumor efficacy of 10D1-CD99 and importantly, its ability in crossing the blood-brain-barrier and reaching the pons target site. Loco-regional administration of 10D1 showed similar anti-tumor effects even at much reduced antibody concentrations while toxicity to CD99-expressing T cells was minimum. Radiation increased CD99 expression and enhanced the cytotoxic effect of 10D1-CD99. CONCLUSION: We have developed a novel CNS penetrant CD99 antibody that is an attractive therapeutic strategy in treating DMG. 10D1 is currently in development as a therapeutic.